Effect of plasma nitriding on the wear and corrosion properties of hastelloy CW2M super-alloy - Casteletti, Luiz Carlos; Fernandes, Frederico Augusto Pires; Heck, Stênio Cristaldo; Picon, Carlos Alberto [UNESP]; Totten, George Edward (My University, 2010)
Hastelloy C alloys are widely used in chemical, aerospace and nuclear industries in corrosive environments. The predominant alloying element of these alloys is typically nickel, although other elements are added. Plasma nitriding is an efficient surface treatment to increase wear resistance. The objective of this work was to evaluate the influence of nitriding treatment on the wear and corrosion properties of the Hastelloy CW2M super-alloy. Hastelloy CW2M was plasma nitrided using the direct current method with the following conditions: a gas mixture of 80 vol. %H2 and 20 vol. %N2, a pressure of 500Pa, temperature of 450 and 500°C, and a treatment time of 5h. As cast and plasma treated samples were analyzed using scanning electron microscopy, wear and corrosion tests. Plasma nitriding of Hastelloy CW2M produced a homogeneous layer with high hardness. X-ray diffraction revealed a γ (fcc) phase for the un-nitrided CW2M. The nitriding at 450°C yielded the appearance of chromium and molybdenum nitrides peaks and possibly an expanded phase; and at 500°C an increase on the chromium and molybdenum nitrides peaks was observed. The wear of samples nitrided at 450 and 500°C were almost 10 times lower than the substrate's wear, which indicates a great improvement on tribological properties. The corrosion parameters showed that although the corrosion potential goes toward positive potentials, increasing nitriding temperature, the corrosion current moves in the opposite direction. Nitriding at 450°C promoted a good corrosion protection with a low open circuit potential value and low corrosion potential. Copyright © (2010) by Associação Brasileira de Metalurgia Materiais e Mineração (ABM).
Keywords: Corrosion; Hatelloy C; Plasma nitriding; Wear